Unique self-assembling biomorphic hierarchic properties of SiO2-nanostructures; International Multidisciplinary Joint Meeting 2013 - Martynyuk O. A. Oksana Anatolievna; Bogdanchikova N.; Ruiz F.; Luna R. V. G.; Huerta A. S.; Zepeda T. A.; Pestryakov A. N. Aleksey Nikolaevich (2013, 2013)
В фонде НТБ ТПУ отсутствует